FACTORS FOR IMPROVING PROTECTION OPTOELECTRONIC DEVICES - SOLAR PANELS - NAKASHYDZE, LILIYA; MAZURYK, STANISLAV; KORSUNSKYI, RODION (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The work presents a study of the physical and technological approach to the solar panels protection to prevent local overheating of electrical origin, which occur because of mismatch of photocurrents in serial connections of solar elements. It is determined that the currently used widely known methods lead to a significant increase in the massive parameters of photoelectric installations. Modern methods of protecting solar installations, such as the use of diodes or active protection systems, are not universal approaches to solving the problem. Therefore, the approach is relevant to the authors on the development and research of solar protection methods. Thus, it is advisable to use polymer-composing devices, which similarly to traditional fuses, limit the flow of dangerously high reverse current during the inconsistency of electrical indicators in the solar panel. The work conducted the study that determines the effect of self-renovation polymer-composing fuses on photoelectric characteristics of the solar battery. In addition, there was done analysis to determine the prospect of using PPTC-cards as elements of thermal protection of solar panels. It has been found that polymer composites are capable of functioning as multiple fuses that do not affect the solar battery and are able to effectively isolate solar elements by performing the function of transition into an inferior state in emergencies associated with the heating of the P-N structure of the photoelement. It is experimentally established that polymer-composing fuses are able to effectively isolate the solar elements, turning to a low-conduct in emergencies associated with the heating of the solar element. The prospects of the solar panel with a two -layer structure of the polymer composite and the solar element in commercial installations are analyzed. In particular, the long-term return of fuses to a high-conducting state and a high temperature of the beginning of the phase transition of the material, which limits the use of polymer-composing fuses for electric heat protection of solar cells, especially in regions with temperate climates.
Keywords: Solar batteries; polymer composites; fuses; photocurrent